Ergonomic garment design for a seamless instrumented swimsuit - Montagna, Gianni (2012)
In the relationship of the human body with the environment, there is no doubt that garments are the most used medium and the most widespread way of communication. In sports garments and in technical apparel, the relationship with the user is even closer, in order to obtain better results and an advantage that could derive from the best combination between the user and the study object. In this paper, the study of different factors affecting athlete’s swimming performance are analyzed. The factors related to textile substrate measure of the swimsuit, as well as the construction methods are taken into account for an optimal design.